Kerguelen Plateau sediment Drift, seismic reflection profile AWI-20200007 - Gabriele Uenzelmann-Neben (PANGAEA, 2021)
Field data (SEGD) of seismic reflection profile AWI-20200007 collected during project Kerguelen Plateau Sediment Drifts with RV Sonne cruise SO272 in 2020. Unprocessed data collected with 3000 m digital streamer, 4 GI-guns were used as seismic source every 25 m. See cruise report of SO272 and readme file 20200007_segd_info for further details on acquisition parameters.